2009
DOI: 10.1017/s0007114509297170
|View full text |Cite
|
Sign up to set email alerts
|

Independent and interactive effects of plant sterols and fish oiln-3 long-chain polyunsaturated fatty acids on the plasma lipid profile of mildly hyperlipidaemic Indian adults

Abstract: The present study was designed to evaluate the independent and interactive effects of a once-a-day yoghurt drink providing 2 g plant sterols/d and capsules providing 2 g fish oil n-3 long-chain (LC) PUFA/d on plasma lipids, apolipoproteins and LDL particle size. Following a 2-week run-in period, 200 mildly hypercholesterolaemic Indian adults aged 35-55 years were randomised into one of four groups of a 2 £ 2 factorial, double-blind controlled trial. The 4-week treatments consisted of (1) control yoghurt drink … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…3. We confirm previous results showing that the reduction in LDL-Chol by PS consumption was not accompanied by a shift in LDL particle distribution [6,12,13], which may largely be ascribed to the lack of changes in total TG [4] and in TG in all LP particles. Considering that TGs are exchanged for cholesterol between TG-rich particles and HDL through cholesterol ester transfer protein (CETP) activity, the unaltered TG concentrations are also in line with the unaltered Chol concentrations in the HDL particles found in this and other studies [27,28].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…3. We confirm previous results showing that the reduction in LDL-Chol by PS consumption was not accompanied by a shift in LDL particle distribution [6,12,13], which may largely be ascribed to the lack of changes in total TG [4] and in TG in all LP particles. Considering that TGs are exchanged for cholesterol between TG-rich particles and HDL through cholesterol ester transfer protein (CETP) activity, the unaltered TG concentrations are also in line with the unaltered Chol concentrations in the HDL particles found in this and other studies [27,28].…”
Section: Discussionsupporting
confidence: 91%
“…The effects of dietary n-3 PUFAs on LDL particles are less consistent. While some studies have shown a favorable shift in LDL particle distribution from small to large LDL particles [18,19], other studies have either found no effects on LDL-Chol [6,17] or an increase in LDL-Chol without concomitant changes in LDL particle size distribution [20].…”
Section: Introductionmentioning
confidence: 99%
“…Khandelwal et al (32) 338 adult men 30-y follow-up survey of the Dutch and Finnish cohorts of the Seven Countries Study…”
Section: Nonementioning
confidence: 99%
“…Thereby, addition of camelina oil improves the overall fatty acid composition of the diet, and it has been shown to lower cholesterol in a comparable manner to rapeseed oil [ 34 ]. Long chain omega-3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) lower serum triglycerides, also when consumed together with plant sterols [ 11 , 35 , 36 ]. The combination of plant sterols and EPA and DHA has also been suggested to enhance the cholesterol lowering effect of plant sterols [ 35 ].…”
Section: Discussionmentioning
confidence: 99%